Strategi Komunikasi Persuasif Lewat Pemutaran Film Pendek Merdeka Belajar di Desa Duawutun Kecamatan Nagawutung Kabupaten Lembata - Maurice Adela Lusiany Watu Due; Yulianto Ulu; Farentino Paulka Keo; P. Yoseph Riang (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2025)
Communication is an important interaction that plays a role in conveying messages effectively. One form of persuasive communication is the use of short films as an educational medium. This research was conducted in Duawutun Village, Lembata Regency, to educate the public about the importance of social media as a useful communication tool. The implementation method involved three stages: planning, preparation, and implementation, with a focus on screening short films with the theme of Merdeka Belajar. The results of the activity showed that short films are an effective tool for conveying educational messages, raising awareness, and motivating changes in attitudes. The use of rational action theory in this approach supports the success of persuasive communication. Short films that are emotional and relevant to the audience have been shown to influence perceptions and behavior, while providing insight into the concept of Merdeka Belajar-based education.